Primary hepatic extranodal marginal zone B-cell mucosa-associated lymphoid tissue lymphoma treated by laparoscopic partial hepatectomy: a case report - Keisuke Okura; Satoru Seo; Hironori Shimizu; Hiroto Nishino; Tomoaki Yoh; Ken Fukumitsu; Takamichi Ishii; Koichiro Hata; Hironori Haga; Etsuro Hatano (Surgical Case Reports, 2023)
Abstract Background Primary hepatic extranodal marginal zone B-cell mucosa-associated lymphoid tissue (MALT) lymphoma is very rare, so it is difficult to diagnose preoperatively. And there is no established treatment for hepatic MALT lymphoma. We report herein a case of primary hepatic MALT lymphoma treated by laparoscopic partial hepatectomy, and discuss the usefulness of laparoscopic hepatectomy for a rare liver tumor. Case presentation This patient was a woman in her 60s, who was diagnosed preoperatively as having synchronous liver metastasis from sigmoid colon cancer; therefore, laparoscopic partial hepatectomy was performed. She had a good course after the operation and was discharged on postoperative day 12. However, she was diagnosed pathologically as having primary hepatic MALT lymphoma. A bone marrow biopsy was also performed, and then she was finally diagnosed as having limited-stage primary hepatic MALT lymphoma. She received no postoperative treatment and showed no recurrence for 4 years postoperatively. Conclusions We experienced the good result of the patient with limited-stage primary MALT lymphoma treated by laparoscopic partial hepatectomy. Liver tumors are sometimes misdiagnosed by imaging examinations alone. Laparoscopic hepatectomy has been widespread recently as a minimally invasive procedure, and it may be useful for both diagnosis and treatment.